The attributes of Shariah compliance practices in hotel industry / Siti Nur’Atikah Latif and Nurul Ain Azmi - Latif, Siti Nur’Atikah; Azmi, Nurul Ain (2020)
The number of Muslim tourists has increased over the years as the number of Muslims with a higher segment of the more educated and prosperous Muslim community has increased. While it is certainly an opportunity for the hotel industry, Islamic hospitality, which creates shariah-compliant hotel standards, has been challenging for hoteliers with Muslim religion and culture. Islamic customers are very large and Muslim visitors around the world are increasingly demanders and even in the face of difficulties the concept of Islamic Hotel is welcomed. Therefore, the objective of this study is to identify the attributes of Shariah compliance practices in the hotel industry and to determine the Shariah compliance attribute that mostly practiced by the hotel industry.